Does EU regional policy increase parties' support for European integration?. Issue 3 (4th May 2018) - Gross, Martin; Debus, Marc
Abstract: How does EU funding to European regions affect sub-national parties' support for European integration? This paper aims at analysing whether the EU regional development policy contributes to setting up support for EU institutions and European integration and thus strengthens the whole 'European idea' among political parties. To answer this research question, the article analyses election manifestos of parties acting on the regional level in Germany, the Netherlands, Spain and the UK for two EU programming periods: 2007─2013 and 2014─2020. The results show that sub-national parties are more supportive of European integration if regions receive more EU funding and if the parties represent regions that are dependent on EU funding.